Notifications for Collaborative Documents Editing: An Augmented Object Approach - López, Gustavo; Guerrero, Luis A. (Ubiquitous Computing and Ambient Intelligence. Personalisation and User Adapted Services, 2014)
In a collaborative writing session one of the most important activities is the notification to all the collaborators about changes in documents (data awareness). In this paper we propose the use of an augmented object as the mechanism to notify changes in shared documents. In this way, collaborators can be aware of modifications even if they are not in front of the computer. A prototype was implemented and evaluated. The augmented object prototype can be used with the Google Docs suite, which permits the collaborators to work in a distributed and asynchronous way.